Social interactions between students and parents in home-based digital-assisted studies - FATİH PALA (Obra Digital, 2025)
The purpose of this study was to examine how young children and their parents interacted during digital activities at home. Researchers conducted a total of 40 home visits to observe the social interactions between children and their parents during digital activities. These interactions were categorized into two main groups: conflict and harmony. Conflicts were resolved through three different solution strategies: parent yielding, child yielding, or compromise. This study demonstrated that parents' consistent interactions significantly enriched children's digital activities. Whether involving conflicts or harmony, social interactions between children and parents provided opportunities for children to enhance their skills in understanding and regulating emotions.